2023
DOI: 10.1021/acsami.2c18989
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Polymerized MXene/Polypyrrole/Hydroxyethyl Cellulose-Based Flexible Strain Sensor Enabled by Machine Learning for Handwriting Recognition

Abstract: Flexible strain sensors have significant progress in the fields of human–computer interaction, medical monitoring, and handwriting recognition, but they also face many challenges such as the capture of weak signals, comprehensive acquisition of the information, and accurate recognition. Flexible strain sensors can sense externally applied deformations, accurately measure human motion and physiological signals, and record signal characteristics of handwritten text. Herein, we prepare a sandwich-structured flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(37 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…In addition, electrical stability of the CNT/MXene/CNT/TPU strain sensor is further characterized by the I – V curve under different stretching (Figure S6) and the Δ R / R 0 -strain curve at different stretching rates (Figure S7), which enable the sensor to accurately and timely transmit the signals captured in human motion detection to back-end processing equipment. Additionally, the performances of the CNT/MXene/CNT/TPU strain sensor and recent crack-based strain sensors are compared in terms of sensing range and sensitivity (Figure h), ,, and the detailed parameters are shown in Table S1. It can be found that crack-based strain sensors are generally unable to combine a wide sensing range and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, electrical stability of the CNT/MXene/CNT/TPU strain sensor is further characterized by the I – V curve under different stretching (Figure S6) and the Δ R / R 0 -strain curve at different stretching rates (Figure S7), which enable the sensor to accurately and timely transmit the signals captured in human motion detection to back-end processing equipment. Additionally, the performances of the CNT/MXene/CNT/TPU strain sensor and recent crack-based strain sensors are compared in terms of sensing range and sensitivity (Figure h), ,, and the detailed parameters are shown in Table S1. It can be found that crack-based strain sensors are generally unable to combine a wide sensing range and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…0D nanoparticles (e.g., metal nanoparticles) have weak inter-particle forces and are at risk of peeling off during long-term use of the sensor . 1D nanomaterials [e.g., carbon nanotubes (CNTs) and metal nanowires] have a large aspect ratio, and the conductive network is better maintained during stretching, exhibiting a high stretching range and low sensitivity. , 2D nanomaterials (e.g., MXene and graphene) have a lamellar structure with a relatively low aspect ratio and cannot slide relative to each other between adjacent sheets, exhibiting high sensitivity and low stretch. , Therefore, it is difficult to achieve comprehensive detection of human motion using a single conductive material. Using different dimensional conductive fillers to form a uniform and continuous cooperative conductive network structure is a common strategy to improve the performance of conductive networks. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al reported a flexible sensor in situ polymerized Ti 3 C 2 F x /polypyrrole/hydroxyethyl cellulose. Polypyrrole (PPy) was introduced as the conductive material to enhance the sensor’s detection range …”
Section: Introductionmentioning
confidence: 99%
“…Polypyrrole (PPy) was introduced as the conductive material to enhance the sensor's detection range. 46 Herein, we successfully prepared the few-layer Ti 3 C 2 F x by HF/LiF etching, DMSO intercalation, ultrasonic exfoliation, and centrifugal separation. 47 Then, PPy nanowires were polymerized in situ via cetyltrimethylammonium bromide (CTAB) micelles as a soft template under the ice bath.…”
Section: Introductionmentioning
confidence: 99%